Composite film with multi-layer flame-retardant space and preparation and application thereof

CN116674238BActive Publication Date: 2026-10-09FUZHOU UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310713151.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-16
Publication Date
2026-10-09
Estimated Expiration
2043-06-16

AI Technical Summary

Technical Problem

由于木质素主要是由苯丙烷基化合物无规则排列聚合成的复杂聚合物,其含有羟基、甲氧基等官能团,因此对比其他生物质聚合物,木质素结构稳定难以分解,在日常中通常以焚烧手段处理,难以加以运用

Benefits of technology

本发明先通过苯甲腈与双氰胺制备苯代三聚氰胺BG作为气源,通过木质素接枝的苯磷酰二氯LF-BPOD作为碳源与酸源,通过混合机将BG与LF-BPOD按一定比例进行混合得到BG/LF-BOPD,然后将其添加到TPU膜材中制成阻燃TPU膜层;同时通过葡萄糖为碳源、植酸为磷源、三乙胺为氮源通过水热法制备磷氮掺杂量子点NP-CQDs溶液,并用其浸泡聚酯纤维得到阻燃聚酯纤维;再通过PUR胶黏剂将阻燃TPU膜层与阻燃聚酯纤维贴合制备成具有多层阻燃空间复合膜层。其中,苯磷酰二氯(BPOD)与木质素(LF)接枝能够很好的除去Cl元素,以制备出无卤阻燃剂;通过双氰胺与苯甲腈制备的苯代三聚氰胺具备三嗪结构,使其在阻燃作用中起到气相阻燃及凝聚相阻燃的作用;NP-CQDs溶液对比于纯量子点溶液,含有N元素及P元素,且其本身具备类石墨烯结构,在阻燃中能够起到协同阻燃的作用。此外,多层阻燃空间复合膜层与单一阻燃TPU膜层、阻燃聚酯纤维相比,其所添加的阻燃剂比例较小,具备更佳的阻燃效果。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116674238B_ABST
    Figure CN116674238B_ABST
Patent Text Reader

Abstract

The application discloses a composite film with multiple layers of flame-retardant space and a preparation method and application thereof, which is prepared from benzene cyanamide prepared from benzyl cyanide and dicyandiamide as a gas source, and lignin grafted benzene phosphoric dichloride as a carbon source and an acid source, and an intumescent flame retardant is formed by compounding the two, and then the intumescent flame retardant is prepared into a flame-retardant TPU film layer; meanwhile, a phosphorus-nitrogen doped quantum dot solution is prepared from glucose as a carbon source, phytic acid as a phosphorus source and triethylamine as a nitrogen source, and polyester fibers are soaked in the solution to prepare flame-retardant polyester fibers; and the obtained flame-retardant TPU film layer and the flame-retardant polyester fibers are hot-pressed and cold-pressed to prepare the composite film with multiple layers of flame-retardant space. The composite film with multiple layers of flame-retardant space has excellent flame-retardant performance, can be used for preparing an air boat, and can generate huge economic benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polymer composite materials, specifically relating to a composite membrane with multi-layer flame-retardant spaces, its preparation method, and its application. Background Technology

[0002] Thermoplastic polyurethane elastomer (TPU) is a linear polymer obtained by block copolymerization of diisocyanate, small molecule polyol, and large molecule polyester or polyether polyol. It has been widely used in adhesives, coatings, composite materials, and biomedical materials. However, with the development of science and technology, higher requirements have been placed on the flame retardant properties of TPU composites in some fields, such as sporting goods. Like many polymers, TPU is easily flammable and produces drippings, toxic gases, and black smoke when burning at high temperatures, potentially triggering more serious fires and causing incalculable losses. Therefore, flame retardant modification of TPU is necessary, and the melting point of the flame retardant must be compatible to ensure its stability during processing.

[0003] Polyester fiber is a basic raw material for textiles, with its main product being polyethylene terephthalate (PET, also known as polyester fiber or polyester). Polyester fiber is widely used in textiles, apparel, home textiles, and industrial applications due to its overall cost-effectiveness. However, due to its chemical structure and combustion characteristics, PET polyester fiber is a flammable material with a relatively low limiting oxygen index (LOI) (approximately 20-22%), and its ignition temperature is close to its decomposition temperature. PET polyester fiber burns violently, and the flame does not extinguish itself, posing a significant threat to the life and property of users.

[0004] Benzyl melamine, also known as benzyl guanine, is a triazine nucleus compound with the same structure as melamine. It is also a commonly used specialty chemical that has been widely used in the preparation of thermosetting resins, modified resins, amino coatings, plastics, pharmaceuticals, pesticides and dyes.

[0005] Benzyl dichloro (BPOD) is used in the production of phenylphosphonic acid and dimethyl phenylphosphonate. It undergoes dehydrochlorination condensation with hydroquinone to produce flame-retardant phosphorus-containing polymers and is used as a heat stabilizer for polyesters; in the presence of pyridine, it reacts with octanol to produce octyl phenylphosphonate, which can be used as a low-volatility plasticizer.

[0006] Lignin (LF), a biomass polymer, is rich in natural aromatics and inexpensive. It is composed of three different alcohol monomers (p-coumarol, coniferol, and sinapyl alcohol), mainly interconnected by ether bonds and carbon-carbon single bonds to form a dense network structure. Because lignin is primarily a complex polymer formed by the random arrangement of phenylpropane compounds, containing functional groups such as hydroxyl and methoxy groups, it is structurally stable and difficult to decompose compared to other biomass polymers. In daily life, it is typically disposed of by incineration, making its application difficult. The pyrolysis temperature of LF ranges from 150-275 °C, continuing up to 700 °C. Under inert gas conditions, it forms a char residue containing 30-50 wt%, exhibiting good carbon-forming ability.

[0007] Quantum dots (CQDs) are novel inorganic nanomaterials that have attracted much attention in recent years. Also known as carbon dots or carbon nanodots, they have a particle size of less than 10 nm. Unmodified CQDs are mainly composed of C, H, and O elements. The carbon atoms in CQDs are primarily composed of sp atoms. 2 and sp 3 Hybrid composition: Since CQDs contain functional groups such as carboxyl and hydroxyl groups on their surface, they can be further modified and their functional groups altered to give them different functionalities. The preparation methods of CQDs are usually "top-down" and "bottom-up". The former mainly uses organic molecules as carbon sources and is prepared through chemical reactions, usually using hydrothermal synthesis, chemical oxidation, microwave synthesis and other methods. Summary of the Invention

[0008] To address the shortcomings of existing technologies, this invention provides a composite membrane with multiple flame-retardant spaces, its preparation method, and its applications. The resulting composite membrane possesses excellent flame-retardant properties, and its application in the field of sporting goods can generate significant economic benefits.

[0009] To achieve the above objectives, the present invention adopts the following technical solution: A composite membrane with multiple flame-retardant spaces is prepared by the following steps: 1) Using benzonitrile and dicyandiamide to prepare benzoic acid melamine (BG) as nitrogen source, and lignin-grafted phenylphosphoryl dichloride (LF-BPOD) as carbon source and acid source, the two are compounded to form an intumescent flame retardant (BG / LF-BOPD), which is then melt-blended with TPU, extruded and granulated to make flame retardant TPU masterbatch, and then cast to obtain flame retardant TPU film layer; 2) Polyester fibers were impregnated with a phosphorus-nitrogen doped quantum dot (NP-CQDs) solution prepared with glucose as carbon source, triethylamine as nitrogen source and phytic acid as phosphorus source to obtain flame-retardant polyester fibers. 3) A layer of flame-retardant polyester fiber is laid between two flame-retardant TPU film layers, and then cold-pressed after hot pressing to form the composite film with multiple flame-retardant spaces.

[0010] Furthermore, the specific preparation steps of the intumescent flame retardant described in step 1) are as follows: a) Add potassium hydroxide to n-butanol and sonicate for 0.5 h to fully dissolve the potassium hydroxide. Then add benzonitrile and dicyandiamide and transfer to an oil bath. React at 110 °C for 2 h under reflux cooling. During this period, a white fine solid gradually precipitates out. Then stop heating and cool to room temperature. Wash the obtained product with deionized water several times to remove unreacted dicyandiamide. Dry at 60 °C for 24 h to obtain benzo-melamine (BG). b) Lignin was dissolved in N,N-dimethylformamide (DMF) and sonicated to ensure complete dissolution. The solution was then transferred to a water bath. Under a nitrogen atmosphere, triethylamine was used as an acid-binding agent, and a DMF dispersion of phenylphosphonodichlorodichloride (BPOD) was slowly added dropwise over 0.5 h. The reaction was then carried out under condensation, a nitrogen atmosphere, and at 80 °C for 5 h. After the reaction was completed, the mixture was cooled to room temperature and centrifuged. The resulting product was washed with chloroform, anhydrous ethanol, and deionized water to remove unreacted BPOD. The product was then freeze-dried to obtain lignin-grafted phenylphosphonodichlorodichloride. c) Mix the benzotricyanate obtained in step a) with the lignin-grafted phenylphosphodichloro obtained in step b) in a certain proportion to obtain the intumescent flame retardant.

[0011] Furthermore, the molar ratio of benzonitrile to potassium hydroxide and dicyandiamide used in step a) is 1:0.18:1.21.

[0012] Furthermore, the mass ratio of lignin to triethylamine and phenylphosphine dichloride used in step b) is 1:4:4.

[0013] Furthermore, in step c), the mass ratio of benzotrimelamine to lignin-grafted phenylphosphine dichloride is 5:5.

[0014] Furthermore, the melt blending described in step 1) is performed by stirring and mixing at room temperature for 0.5 hours using a high-speed mixer.

[0015] Furthermore, during the extrusion granulation described in step 1), the temperature of the feeding section of the twin-screw granulator is 100-110℃, the temperature of the mixing section is 125-135℃, the temperature of the extrusion section is 150-160℃, and the temperature of the die head is 130-140℃.

[0016] Further, the process parameters for casting described in step 1) are: roller diameter 500 mm, roller temperature 45℃, pressure winding on a 60-54A liquid silicone roller, and pressure of 6 Kgf.

[0017] Furthermore, the intumescent flame retardant in the flame-retardant TPU film obtained in step 1) accounts for 3-7% by weight.

[0018] Further, in step 2), the preparation of the phosphorus-nitrogen doped quantum dot solution involves dissolving glucose, phytic acid, and triethylamine together in deionized water, stirring at room temperature for 0.5 h, transferring the solution to a polytetrafluoroethylene reactor, and performing a hydrothermal reaction at 160°C for 6 h. Insoluble substances are then removed by filtration, and the resulting filtrate is dialyzed in a dialysis bag for 48 h. The ratio of glucose, phytic acid, and triethylamine used is 1 g: 0.8 mL: 0.5 mL. The hydrothermal reaction temperature is 160°C, and the reaction time is 6 h.

[0019] Furthermore, the weight percentage of phosphorus and nitrogen-doped quantum dots in the flame-retardant polyester fiber obtained in step 2) is 3-7%.

[0020] Furthermore, the hot pressing temperature in step 3) is 150°C and the time is 150 min.

[0021] Furthermore, the cold pressing temperature in step 3) is room temperature, and the time is 10 minutes.

[0022] The resulting composite membrane with multiple flame-retardant spaces can be used to manufacture inflatable boats for sports equipment.

[0023] The beneficial effects of this invention are as follows: This invention first prepares benzoic acid melamine (BG) using benzonitrile and dicyandiamide as a gas source, and uses lignin-grafted phenylphosphoryl dichloride (LF-BPOD) as a carbon and acid source. BG and LF-BPOD are mixed in a certain proportion using a mixer to obtain BG / LF-BOPD, which is then added to TPU film to form a flame-retardant TPU film layer. Simultaneously, a phosphorus-nitrogen doped quantum dot (NP-CQDs) solution is prepared via a hydrothermal method using glucose as a carbon source, phytic acid as a phosphorus source, and triethylamine as a nitrogen source. This solution is then used to impregnate polyester fibers to obtain flame-retardant polyester fibers. Finally, the flame-retardant TPU film layer and the flame-retardant polyester fibers are bonded together using PUR adhesive to prepare a multi-layered flame-retardant spatial composite film layer. Among these methods, grafting phenylphosphamide dichloride (BPOD) with lignin (LF) effectively removes chloride (Cl) to prepare halogen-free flame retardants. The benzoic melamine prepared from dicyandiamide and benzonitrile possesses a triazine structure, enabling it to act as both a gas-phase and condensed-phase flame retardant. Compared to pure quantum dot solutions, NP-CQDs solutions contain nitrogen (N) and phosphorus (P) elements and possess a graphene-like structure, thus exhibiting a synergistic flame-retardant effect. Furthermore, compared to single flame-retardant TPU films and flame-retardant polyester fibers, multilayer flame-retardant spatial composite films require a smaller proportion of added flame retardants, resulting in superior flame-retardant performance. Attached Figure Description

[0024] Figure 1 Infrared images of BG, LF, LF-BPOD, and NP-CQDs prepared in Example 5.

[0025] Figure 2 The image shows the XRD patterns of BG, LF, LF-BPOD, and NP-CQDs prepared in Example 5.

[0026] Figure 3 SEM images of BG, LF, LF-BPOD, pure polyester fiber, and flame-retardant polyester fiber prepared in Example 5.

[0027] Figure 4 This is a TEM image of the NP-CQDs prepared in Example 5.

[0028] Figure 5 The fluorescence spectrum of the NP-CQDs prepared in Example 5 is shown. Detailed Implementation

[0029] A composite membrane with multiple flame-retardant spaces is prepared by the following steps: 1) Preparation of intumescent flame retardants: a) A certain amount of n-butanol was placed in a 250 mL three-necked flask, potassium hydroxide was added, and the mixture was sonicated for 0.5 h to fully dissolve the potassium hydroxide. Then, benzonitrile and dicyandiamide were added, and the mixture was transferred to an oil bath. The mixture was reacted at 110 °C for 2 h under reflux cooling conditions. During this process, a white fine solid gradually precipitated out. Heating was then stopped, and the mixture was cooled to room temperature. The product was washed several times with deionized water to remove unreacted dicyandiamide, and dried at 60 °C for 24 h to obtain benzoated melamine (BG). The molar ratio of benzonitrile to potassium hydroxide and dicyandiamide used was 1:0.18:1.21. b) Lignin was dissolved in N,N-dimethylformamide (DMF) and placed in a 250 mL three-necked flask. The solution was sonicated until fully dissolved, and then transferred to a water bath. Benzophosphonate dichloride (BPOD) was dispersed in DMF under rapid stirring at room temperature and transferred to a separatory funnel. Triethylamine was then added as an acid-binding agent under a nitrogen atmosphere, and the flow rate was controlled so that the BPOD DMF dispersion was slowly added dropwise to the three-necked flask over 0.5 h. The reaction was then carried out under condensation, a nitrogen atmosphere, and at 80 °C for 5 h. After the reaction was complete, the mixture was cooled to room temperature and centrifuged. The resulting product was washed with chloroform, anhydrous ethanol, and deionized water to remove excess unreacted BPOD. The purified product was dissolved in deionized water and freeze-dried to obtain lignin-grafted phenylphosphonate dichloride (LF-BPOD). The mass ratio of lignin to triethylamine and phenylphosphonate dichloride used was 1:4:4. c) Add the BG obtained in step a) and the LF-BPOD obtained in step b) to a high-speed mixer at a mass ratio of 5:5, and stir and mix for 0.5 h to obtain an intumescent flame retardant (BG / LF-BOPD). 2) Preparation of flame-retardant TPU film: The BG / LF-BOPD obtained in step 1) and TPU were mixed at room temperature for 0.5 hours using a high-speed mixer. Then, they were extruded and granulated using a twin-screw granulator to produce flame-retardant TPU masterbatch. The masterbatch was then cast to obtain a flame-retardant TPU film. The temperature of the feeding section of the twin-screw granulator was 100-110℃, the temperature of the mixing section was 125-135℃, the temperature of the extrusion section was 150-160℃, and the temperature of the die head was 130-140℃. The roller diameter used for casting was 500 mm, the roller temperature was 45℃, and the film was wound on a 60-54A liquid silicone roller with a pressure of 6 Kgf. 3) Preparation of phosphorus-nitrogen doped quantum dot (NP-CQDs) solution: Glucose, phytic acid, and triethylamine were dissolved together in deionized water and stirred at room temperature for 0.5 h. The solution was then transferred to a polytetrafluoroethylene reactor and subjected to hydrothermal reaction at 160 °C for 6 h. After cooling, insoluble substances were removed by filtration, and the resulting filtrate was dialyzed in a dialysis bag for 48 h to obtain a phosphorus nitrogen-doped quantum dot (NP-CQDs) solution. The mass ratio of glucose, phytic acid, and triethylamine used was 1 g: 0.8 mL: 0.5 mL. 4) Preparation of flame-retardant polyester fibers: The polyester fiber was impregnated with the NP-CQDs solution obtained in step 3) to obtain flame-retardant polyester fiber; 5) Preparation of composite membranes with multi-layered flame-retardant spaces: A layer of flame-retardant polyester fiber is laid between two layers of flame-retardant TPU film, and then the film is placed in a molding machine and hot-pressed at 150°C for 150 minutes, followed by cold pressing at room temperature for 10 minutes to form a composite film with multiple flame-retardant spaces.

[0030] In step 2), the intumescent flame retardant in the flame-retardant TPU film layer accounts for 3-7% by weight.

[0031] Step 4) The weight percentage of phosphorus and nitrogen doped quantum dots in the obtained flame-retardant polyester fiber is 3-7%.

[0032] To make the content of this invention easier to understand, the technical solution of this invention will be further described below with reference to specific embodiments, but this invention is not limited thereto.

[0033] Example 1 A composite membrane with multiple flame-retardant spaces is prepared by the following steps: 1) Preparation of intumescent flame retardants: a) Place 50 mL of n-butanol in a 250 mL three-necked flask, add 1.25 g (0.022 mol) of potassium hydroxide, sonicate for 0.5 h to fully dissolve the potassium hydroxide, then add 12.6 g (0.122 mol) of benzonitrile and 12.5 g (0.148 mol) of dicyandiamide, and transfer to an oil bath. React at 110 °C for 2 h under reflux cooling conditions. During this period, a white fine solid gradually precipitates out. Then stop heating, cool to room temperature, and wash the product with deionized water several times to remove unreacted dicyandiamide. Dry at 60 °C for 24 h to obtain BG. b) Dissolve 1 g of lignin in 60 mL of DMF and place it in a 250 mL three-necked flask. Sonicate the solution until fully dissolved, and then transfer it to a water bath. Under rapid stirring at room temperature, disperse 4 g of BPOD in 20 mL of DMF and transfer it to a separatory funnel. Then, under a nitrogen atmosphere, add 4 g of triethylamine as an acid-binding agent and control the flow rate so that the BPOD DMF dispersion is slowly added dropwise to the three-necked flask over 0.5 h. React under condensation, nitrogen atmosphere, and 80 °C for 5 h. After the reaction is complete, cool to room temperature and centrifuge. Wash the product with chloroform, anhydrous ethanol, and deionized water to remove excess unreacted BPOD. Dissolve the purified product in deionized water and freeze-dry to obtain LF-BPOD. c) Add the BG obtained in step a) and the LF-BPOD obtained in step b) to a high-speed mixer at a mass ratio of 5:5, and stir and mix for 0.5 h to obtain BG / LF-BOPD. 2) Preparation of flame-retardant TPU film: 15g of BG / LF-BOPD (3% of the total amount) obtained in step 1) was mixed with 485g of pure TPU masterbatch in a small high-speed mixer at 600r / min for 0.5h. The dried material was then fed into a twin-screw granulator through a side feed port for extrusion granulation to produce flame-retardant TPU masterbatch. After drying at 120℃ for 8h, it was placed in a casting machine to cast a flame-retardant TPU film with a thickness of 0.8mm. The temperature of the feeding section of the twin-screw granulator was 110℃, the temperature of the mixing section was 130℃, the temperature of the extrusion section was 155℃, and the die head temperature was 135℃. The roller diameter used for casting was 500mm, the roller temperature was 45℃, and the film was wound on a 58A liquid silicone roller with a pressure of 6Kgf. 3) Preparation of phosphorus-nitrogen doped quantum dot (NP-CQDs) solution: Weigh 1 g of glucose and place it in a 250 mL beaker. Add 25 mL of deionized water and sonicate for 0.5 h to dissolve it completely. Then add 0.8 mL of phytic acid and 0.5 mL of triethylamine and sonicate for another 0.5 h. Transfer the solution to a polytetrafluoroethylene reactor and place it in a vacuum drying oven. After hydrothermal reaction at 160 °C for 6 h, cool the solution and remove insoluble substances by filtration. Then place the filtrate in a dialysis bag and dialyze for 48 h to obtain the NP-CQDs solution. 4) Preparation of flame-retardant polyester fibers: After impregnating the polyester fiber with the NP-CQDs solution obtained in step 3), the polyester fiber is weighed. When its weight increases by 3%, flame-retardant polyester fiber is obtained. 5) Preparation of composite membranes with multi-layered flame-retardant spaces: A layer of flame-retardant polyester fiber with a thickness of 0.8 mm is laid between two layers of flame-retardant TPU film. Then, it is placed in a molding machine and hot-pressed at 150°C for 150 minutes, followed by cold pressing at room temperature for 10 minutes to form a composite film with multiple flame-retardant spaces.

[0034] Example 2 A composite membrane with multiple flame-retardant spaces is prepared by the following steps: 1) Preparation of intumescent flame retardants: a) Place 50 mL of n-butanol in a 250 mL three-necked flask, add 1.25 g of potassium hydroxide, and sonicate for 0.5 h to fully dissolve the potassium hydroxide. Then add 12.6 g of benzonitrile and 12.5 g of dicyandiamide, and transfer to an oil bath. React at 110 °C for 2 h under reflux cooling. During this period, a white fine solid gradually precipitates out. Then stop heating, cool to room temperature, and wash the product with deionized water several times to remove unreacted dicyandiamide. Dry at 60 °C for 24 h to obtain BG. b) Dissolve 1 g of lignin in 60 mL of DMF and place it in a 250 mL three-necked flask. Sonicate the solution until fully dissolved, and then transfer it to a water bath. Under rapid stirring at room temperature, disperse 4 g of BPOD in 20 mL of DMF and transfer it to a separatory funnel. Then, under a nitrogen atmosphere, add 4 g of triethylamine as an acid-binding agent and control the flow rate so that the BPOD DMF dispersion is slowly added dropwise to the three-necked flask over 0.5 h. React under condensation, nitrogen atmosphere, and 80 °C for 5 h. After the reaction is complete, cool to room temperature and centrifuge. Wash the product with chloroform, anhydrous ethanol, and deionized water to remove excess unreacted BPOD. Dissolve the purified product in deionized water and freeze-dry to obtain LF-BPOD. c) Add the BG obtained in step a) and the LF-BPOD obtained in step b) to a high-speed mixer at a mass ratio of 5:5, and stir and mix for 0.5 h to obtain BG / LF-BOPD. 2) Preparation of flame-retardant TPU film: 20g of BG / LF-BOPD (4% of the total amount) obtained in step 1) was mixed with 480g of pure TPU masterbatch in a small high-speed mixer at 600r / min for 0.5h. The dried material was then fed into a twin-screw granulator through a side feed port for extrusion granulation to produce flame-retardant TPU masterbatch. After drying at 120℃ for 8h, it was placed in a casting machine to cast a flame-retardant TPU film with a thickness of 0.8mm. The temperature of the feeding section of the twin-screw granulator was 110℃, the temperature of the mixing section was 130℃, the temperature of the extrusion section was 155℃, and the die head temperature was 135℃. The roller diameter used for casting was 500mm, the roller temperature was 45℃, and the film was wound on a 58A liquid silicone roller with a pressure of 6Kgf. 3) Preparation of phosphorus-nitrogen doped quantum dot (NP-CQDs) solution: Weigh 1 g of glucose and place it in a 250 mL beaker. Add 25 mL of deionized water and sonicate for 0.5 h to dissolve it completely. Then add 0.8 mL of phytic acid and 0.5 mL of triethylamine and sonicate for another 0.5 h. Transfer the solution to a polytetrafluoroethylene reactor and place it in a vacuum drying oven. After hydrothermal reaction at 160 °C for 6 h, cool the solution and remove insoluble substances by filtration. Then place the filtrate in a dialysis bag and dialyze for 48 h. Freeze dry to obtain NP-CQDs solution. 4) Preparation of flame-retardant polyester fibers: After impregnating the polyester fiber with the NP-CQDs solution obtained in step 3), the polyester fiber is weighed. When its weight increases by 4%, flame-retardant polyester fiber is obtained. 5) Preparation of composite membranes with multi-layered flame-retardant spaces: A layer of flame-retardant polyester fiber with a thickness of 0.8 mm is laid between two layers of flame-retardant TPU film. Then, it is placed in a molding machine and hot-pressed at 150°C for 150 minutes, followed by cold pressing at room temperature for 10 minutes to form a composite film with multiple flame-retardant spaces.

[0035] Example 3 A composite membrane with multiple flame-retardant spaces is prepared by the following steps: 1) Preparation of intumescent flame retardants: a) Place 50 mL of n-butanol in a 250 mL three-necked flask, add 1.25 g of potassium hydroxide, and sonicate for 0.5 h to fully dissolve the potassium hydroxide. Then add 12.6 g of benzonitrile and 12.5 g of dicyandiamide, and transfer to an oil bath. React at 110 °C for 2 h under reflux cooling. During this period, a white fine solid gradually precipitates out. Then stop heating, cool to room temperature, and wash the product with deionized water several times to remove unreacted dicyandiamide. Dry at 60 °C for 24 h to obtain BG. b) Dissolve 1 g of lignin in 60 mL of DMF and place it in a 250 mL three-necked flask. Sonicate the solution until fully dissolved, and then transfer it to a water bath. Under rapid stirring at room temperature, disperse 4 g of BPOD in 20 mL of DMF and transfer it to a separatory funnel. Then, under a nitrogen atmosphere, add 4 g of triethylamine as an acid-binding agent and control the flow rate so that the BPOD DMF dispersion is slowly added dropwise to the three-necked flask over 0.5 h. React under condensation, nitrogen atmosphere, and 80 °C for 5 h. After the reaction is complete, cool to room temperature and centrifuge. Wash the product with chloroform, anhydrous ethanol, and deionized water to remove excess unreacted BPOD. Dissolve the purified product in deionized water and freeze-dry to obtain LF-BPOD. c) Add the BG obtained in step a) and the LF-BPOD obtained in step b) to a high-speed mixer at a mass ratio of 5:5, and stir and mix for 0.5 h to obtain BG / LF-BOPD. 2) Preparation of flame-retardant TPU film: 25g of BG / LF-BOPD (5% of the total amount) obtained in step 1) was mixed with 478g of pure TPU masterbatch in a small high-speed mixer at 600r / min for 0.5h. The dried material was then fed into a twin-screw granulator through a side feed port for extrusion granulation to produce flame-retardant TPU masterbatch. After drying at 120℃ for 8h, it was placed in a casting machine to cast a flame-retardant TPU film with a thickness of 0.8mm. The temperature of the feeding section of the twin-screw granulator was 110℃, the temperature of the mixing section was 130℃, the temperature of the extrusion section was 155℃, and the die head temperature was 135℃. The diameter of the roller used for casting was 500mm, the roller temperature was 45℃, and the roller was wound on a 58A liquid silicone roller with a pressure of 6Kgf. 3) Preparation of phosphorus-nitrogen doped quantum dot (NP-CQDs) solution: Weigh 1 g of glucose and place it in a 250 mL beaker. Add 25 mL of deionized water and sonicate for 0.5 h to dissolve it completely. Then add 0.8 mL of phytic acid and 0.5 mL of triethylamine and sonicate for another 0.5 h. Transfer the solution to a polytetrafluoroethylene reactor and place it in a vacuum drying oven. After hydrothermal reaction at 160 °C for 6 h, cool the solution and remove insoluble substances by filtration. Then place the filtrate in a dialysis bag and dialyze for 48 h. Freeze dry to obtain NP-CQDs solution. 4) Preparation of flame-retardant polyester fibers: After impregnating the polyester fiber with the NP-CQDs solution obtained in step 3), the polyester fiber is weighed. When its weight increases by 5%, flame-retardant polyester fiber is obtained. 5) Preparation of composite membranes with multi-layered flame-retardant spaces: A layer of flame-retardant polyester fiber with a thickness of 0.8 mm is laid between two layers of flame-retardant TPU film. Then, it is placed in a molding machine and hot-pressed at 150°C for 150 minutes, followed by cold pressing at room temperature for 10 minutes to form a composite film with multiple flame-retardant spaces.

[0036] Example 4 A composite membrane with multiple flame-retardant spaces is prepared by the following steps: 1) Preparation of intumescent flame retardants: a) Place 50 mL of n-butanol in a 250 mL three-necked flask, add 1.25 g of potassium hydroxide, and sonicate for 0.5 h to fully dissolve the potassium hydroxide. Then add 12.6 g of benzonitrile and 12.5 g of dicyandiamide, and transfer to an oil bath. React at 110 °C for 2 h under reflux cooling. During this period, a white fine solid gradually precipitates out. Then stop heating, cool to room temperature, and wash the product with deionized water several times to remove unreacted dicyandiamide. Dry at 60 °C for 24 h to obtain BG. b) Dissolve 1 g of lignin in 60 mL of DMF and place it in a 250 mL three-necked flask. Sonicate the solution until fully dissolved, and then transfer it to a water bath. Under rapid stirring at room temperature, disperse 4 g of BPOD in 20 mL of DMF and transfer it to a separatory funnel. Then, under a nitrogen atmosphere, add 4 g of triethylamine as an acid-binding agent and control the flow rate so that the BPOD DMF dispersion is slowly added dropwise to the three-necked flask over 0.5 h. React under condensation, nitrogen atmosphere, and 80 °C for 5 h. After the reaction is complete, cool to room temperature and centrifuge. Wash the product with chloroform, anhydrous ethanol, and deionized water to remove excess unreacted BPOD. Dissolve the purified product in deionized water and freeze-dry to obtain LF-BPOD. c) Add the BG obtained in step a) and the LF-BPOD obtained in step b) to a high-speed mixer at a mass ratio of 5:5, and stir and mix for 0.5 h to obtain BG / LF-BOPD. 2) Preparation of flame-retardant TPU film: 30g of BG / LF-BOPD (6% of the total amount) obtained in step 1) was mixed with 470g of pure TPU masterbatch in a small high-speed mixer at 600r / min for 0.5h. Then, the dried material was fed into a twin-screw granulator through the side feed port for extrusion granulation to produce flame-retardant TPU masterbatch. After drying at 120℃ for 8h, it was placed in a casting machine to cast a flame-retardant TPU film with a thickness of 0.8mm. The temperature of the feeding section of the twin-screw granulator was 110℃, the temperature of the mixing section was 130℃, the temperature of the extrusion section was 155℃, and the die head temperature was 135℃. The diameter of the roller used for casting was 500mm, the roller temperature was 45℃, and the roller was wound on a 58A liquid silicone roller with a pressure of 6Kgf. 3) Preparation of phosphorus nitrogen doped quantum dot (NP-CQDs) solution: Weigh 1 g of glucose and place it in a 250 mL beaker. Add 25 mL of deionized water and sonicate for 0.5 h to dissolve it completely. Then add 0.8 mL of phytic acid and 0.5 mL of triethylamine and sonicate for another 0.5 h. Transfer the solution to a polytetrafluoroethylene reactor and place it in a vacuum drying oven. After hydrothermal reaction at 160 °C for 6 h, cool the solution and remove insoluble substances by filtration. Then place the filtrate in a dialysis bag and dialyze for 48 h. Freeze dry to obtain NP-CQDs solution. 4) Preparation of flame-retardant polyester fibers: After impregnating the polyester fiber with the NP-CQDs solution obtained in step 3), the polyester fiber is weighed. When its weight increases by 6%, flame-retardant polyester fiber is obtained. 5) Preparation of composite membranes with multi-layered flame-retardant spaces: A layer of flame-retardant polyester fiber with a thickness of 0.8 mm is laid between two layers of flame-retardant TPU film. Then, it is placed in a molding machine and hot-pressed at 150°C for 150 minutes, followed by cold pressing at room temperature for 10 minutes to form a composite film with multiple flame-retardant spaces.

[0037] Example 5 A composite membrane with multiple flame-retardant spaces is prepared by the following steps: 1) Preparation of intumescent flame retardants: a) Place 50 mL of n-butanol in a 250 mL three-necked flask, add 1.25 g of potassium hydroxide, and sonicate for 0.5 h to fully dissolve the potassium hydroxide. Then add 12.6 g of benzonitrile and 12.5 g of dicyandiamide, and transfer to an oil bath. React at 110 °C for 2 h under reflux cooling. During this period, a white fine solid gradually precipitates out. Then stop heating, cool to room temperature, and wash the product with deionized water several times to remove unreacted dicyandiamide. Dry at 60 °C for 24 h to obtain BG. b) Dissolve 1 g of lignin in 60 mL of DMF and place it in a 250 mL three-necked flask. Sonicate the solution until fully dissolved, and then transfer it to a water bath. Under rapid stirring at room temperature, disperse 4 g of BPOD in 20 mL of DMF and transfer it to a separatory funnel. Then, under a nitrogen atmosphere, add 4 g of triethylamine as an acid-binding agent and control the flow rate so that the BPOD DMF dispersion is slowly added dropwise to the three-necked flask over 0.5 h. React under condensation, nitrogen atmosphere, and 80 °C for 5 h. After the reaction is complete, cool to room temperature and centrifuge. Wash the product with chloroform, anhydrous ethanol, and deionized water to remove excess unreacted BPOD. Dissolve the purified product in deionized water and freeze-dry to obtain LF-BPOD. c) Add the BG obtained in step a) and the LF-BPOD obtained in step b) to a high-speed mixer at a mass ratio of 5:5, and stir and mix for 0.5 h to obtain BG / LF-BOPD. 2) Preparation of flame-retardant TPU film: 35g of BG / LF-BOPD (7% of the total amount) obtained in step 1) was mixed with 465g of pure TPU masterbatch in a small high-speed mixer at 600r / min for 0.5h. The dried material was then fed into a twin-screw granulator through a side feed port for extrusion granulation to produce flame-retardant TPU masterbatch. After drying at 120℃ for 8h, it was placed in a casting machine to cast a flame-retardant TPU film with a thickness of 0.8mm. The temperature of the feeding section of the twin-screw granulator was 110℃, the temperature of the mixing section was 130℃, the temperature of the extrusion section was 155℃, and the die head temperature was 135℃. The roller diameter used for casting was 500mm, the roller temperature was 45℃, and the film was wound on a 58A liquid silicone roller with a pressure of 6Kgf. 3) Preparation of phosphorus-nitrogen doped quantum dot (NP-CQDs) solution: Weigh 1 g of glucose and place it in a 250 mL beaker. Add 25 mL of deionized water and sonicate for 0.5 h to dissolve it completely. Then add 0.8 mL of phytic acid and 0.5 mL of triethylamine and sonicate for another 0.5 h. Transfer the solution to a polytetrafluoroethylene reactor and place it in a vacuum drying oven. After hydrothermal reaction at 160 °C for 6 h, cool the solution and remove insoluble substances by filtration. Then place the filtrate in a dialysis bag and dialyze for 48 h. Freeze dry to obtain NP-CQDs solution. 4) Preparation of flame-retardant polyester fibers: After impregnating the polyester fiber with the NP-CQDs solution obtained in step 3), the polyester fiber is weighed. When its weight increases by 7%, flame-retardant polyester fiber is obtained. 5) Preparation of composite membranes with multi-layered flame-retardant spaces: A layer of flame-retardant polyester fiber with a thickness of 0.8 mm is laid between two layers of flame-retardant TPU film. Then, it is placed in a molding machine and hot-pressed at 150°C for 150 minutes, followed by cold pressing at room temperature for 10 minutes to form a composite film with multiple flame-retardant spaces.

[0038] Figure 1 Infrared spectra of the prepared BG, LF, LF-BPOD, and NP-CQDs are shown. From the images, it can be observed that BG exhibits the following characteristics at 1246 cm⁻¹. -1 and 685 cm -1 The absorption peak at [location] is a characteristic absorption peak of the benzene ring skeleton, which proves that the triazine structure contains a benzene ring, thus proving the successful synthesis of BG; in the infrared spectrum of LF, the broad peak peak region is at 3400 cm⁻¹. -1 ~3300 cm -1 The absorption peak at 1407 cm⁻¹ corresponds to the region of the characteristic -OH peak, while the absorption peaks at 1607 cm⁻¹ and 1406 cm⁻¹ are characteristic peaks of the aromatic ring. From the LF-BPOD infrared spectrum, it can be seen that the absorption peak at 3400 cm⁻¹ corresponds to the region of the characteristic -OH peak. -1 ~3200 cm -1 The enhanced absorption peak intensity at 1607 cm⁻¹ is likely due to the increased moisture content of LF-BPOD during storage, which cannot be completely removed during drying. This leads to an increased intensity of the -OH characteristic peak in LF-BPOD, particularly at 1607 cm⁻¹. -1 With 1406 cm -1 The characteristic peaks at this location are fully preserved, indicating that it retains the relevant characteristic peaks of LF, and the main component is still LF; comparing the infrared spectrum of LF, a new 993 cm⁻¹ peak can be seen in LF-BPOD. -1The absorption peak at 3348 cm⁻¹ is attributed to the characteristic peak of POC, proving that BPOD and LF underwent a grafting reaction to form the POC structure, thus proving the successful grafting of LF and BPOD; the infrared spectrum of NP-CQDs shows that the peak at 3348 cm⁻¹ is... -1 The absorption peak at 3266 cm⁻¹ is a characteristic peak of -OH. -1 The absorption peak at 2906 cm⁻¹ is attributed to the characteristic peak of NH. -1 The absorption peak at 1658 cm⁻¹ is a characteristic peak of CH. -1 The absorption peak at 1556 cm⁻¹ is a characteristic peak of C=O. -1 The absorption peak at 1387 cm⁻¹ is a characteristic peak of C=C. -1 The absorption peak at 1144 cm⁻¹ is a characteristic peak of CN, and the appearance of this peak indicates the successful synthesis of nitrogen-doped quantum dots. -1 The absorption peak at 1052 cm⁻¹ is a characteristic peak of P=O. -1 The absorption peak at 779 cm⁻¹ is a characteristic peak of PO. -1 The absorption peak at 948 cm⁻¹ is attributed to the characteristic peak of POH. -1 The absorption peak at this point is attributed to the characteristic peak of CP. The appearance of this peak indicates the successful synthesis of phosphorus-doped quantum dots. In summary, CN, CP, and their related characteristic peaks prove the successful synthesis of NP-CQDs.

[0039] Figure 2 The XRD patterns of the prepared BG, LF, LF-BPOD, and NP-CQDs are shown in the figure. As can be seen from the figure, the diffraction peaks of BG are consistent with those on the standard card, proving that BG was successfully synthesized; LF has an amorphous structure; LF-BPOD only shows a broad diffraction peak at 11°-22°, indicating an amorphous structure, which shows that the grafting of BPOD and LF does not change the crystal form of LF; the diffraction peaks of NP-CQDs appear at around 22°, which corresponds to the (002) crystal plane and is a carbon peak, confirming the successful synthesis of quantum dots.

[0040] Figure 3 SEM images of the prepared BG (a), LF (b), LF-BPOD (c), pure polyester fiber (d), and flame-retardant polyester fiber (e) are shown. As can be seen from the images, the microstructure of BG is blocky (a); LF, due to its high water absorption, shows agglomeration and an amorphous structure (b); LF-BPOD shows blocky objects on the microstructure of lignin, confirming successful BPOD grafting (c); the microstructure of pure polyester fiber is rough and does not contain other substances (d); the microstructure of flame-retardant polyester fiber is relatively smooth and has fine particles loaded on its surface, exhibiting NP-CQDs (e).

[0041] Figure 4 The image shows a TEM image of the prepared NP-CQDs. Fine, round particles can be observed at 200 nm magnification; fine black dots can be observed at 50 nm magnification, indicating that the particle size is less than 10 nm, which is consistent with the size of quantum dots.

[0042] Figure 5 The fluorescence spectrum of the prepared NP-CQDs is shown in the figure. As can be seen from the figure, with a fixed excitation wavelength of 349 nm as the detection wavelength, the test results show that the emission peak reaches its strongest at 364 nm (a); when the excitation wavelength is 364 nm, the emission peak intensity reaches its strongest at 445 nm. Comparing the emission peak intensity obtained by increasing the excitation wavelength by 15 nm from 319 nm, it can be concluded that the emission peak intensity obtained at the excitation wavelength of 364 nm is the strongest. The analysis of the fluorescence spectrum confirms the successful preparation of NP-CQDs and the relationship between the excitation wavelength and the position of the emission peak.

[0043] Comparative Example 1 (pure TPU, pure polyester fiber) (1) Weigh 500g of pure TPU masterbatch, dry it in a forced-air drying oven at 120℃ for 8h, and then place it in a casting machine to cast into a TPU film layer; (2) A layer of pure polyester fiber with a thickness of 0.8 mm is laid between two pure TPU film layers, and then it is placed in a molding machine. After hot pressing at 150°C for 150 min, it is cold pressed at room temperature for 10 min to obtain a multi-layer spatial composite film layer.

[0044] Comparative Example 2 (Flame-retardant TPU film, pure polyester fiber) A composite membrane with multiple flame-retardant spaces is prepared by the following steps: 1) Preparation of intumescent flame retardants: a) Place 50 mL of n-butanol in a 250 mL three-necked flask, add 1.25 g of potassium hydroxide, and sonicate for 0.5 h to fully dissolve the potassium hydroxide. Then add 12.6 g of benzonitrile and 12.5 g of dicyandiamide, and transfer to an oil bath. React at 110 °C for 2 h under reflux cooling. During this period, a white fine solid gradually precipitates out. Then stop heating, cool to room temperature, and wash the product with deionized water several times to remove unreacted dicyandiamide. Dry at 60 °C for 24 h to obtain BG. b) Dissolve 1 g of lignin in 60 mL of DMF and place it in a 250 mL three-necked flask. Sonicate the solution until fully dissolved, and then transfer it to a water bath. Under rapid stirring at room temperature, disperse 4 g of BPOD in 20 mL of DMF and transfer it to a separatory funnel. Then, under a nitrogen atmosphere, add 4 g of triethylamine as an acid-binding agent and control the flow rate so that the BPOD DMF dispersion is slowly added dropwise to the three-necked flask over 0.5 h. React under condensation, nitrogen atmosphere, and 80 °C for 5 h. After the reaction is complete, cool to room temperature and centrifuge. Wash the product with chloroform, anhydrous ethanol, and deionized water to remove excess unreacted BPOD. Dissolve the purified product in deionized water and freeze-dry to obtain LF-BPOD. c) Add the BG obtained in step a) and the LF-BPOD obtained in step b) to a high-speed mixer at a mass ratio of 5:5, and stir and mix for 0.5 h to obtain BG / LF-BOPD. 2) Preparation of flame-retardant TPU film: 35g of BG / LF-BOPD (7% of the total amount) obtained in step 1) was mixed with 465g of pure TPU masterbatch in a small high-speed mixer at 600r / min for 0.5h. The dried material was then fed into a twin-screw granulator through a side feed port for extrusion granulation to produce flame-retardant TPU masterbatch. After drying at 120℃ for 8h, it was placed in a casting machine to cast a flame-retardant TPU film with a thickness of 0.8mm. The temperature of the feeding section of the twin-screw granulator was 110℃, the temperature of the mixing section was 130℃, the temperature of the extrusion section was 155℃, and the die head temperature was 135℃. The roller diameter used for casting was 500mm, the roller temperature was 45℃, and the film was wound on a 58A liquid silicone roller with a pressure of 6Kgf. 3) Preparation of composite membranes with multi-layered flame-retardant spaces: A layer of pure polyester fiber with a thickness of 0.8 mm is laid between two flame-retardant TPU film layers. Then, it is placed in a molding machine and hot-pressed at 150°C for 150 minutes, followed by cold pressing at room temperature for 10 minutes to form a composite film with multiple flame-retardant spaces.

[0045] Comparative Example 3 (pure TPU film, flame-retardant polyester fiber) An internal flame-retardant polyester fiber membrane is prepared by the following steps: 1) Preparation of phosphorus-nitrogen doped quantum dot (NP-CQDs) solution: Weigh 1 g of glucose and place it in a 250 mL beaker. Add 25 mL of deionized water and sonicate for 0.5 h to dissolve it completely. Then add 0.8 mL of phytic acid and 0.5 mL of triethylamine and sonicate for another 0.5 h. Transfer the solution to a polytetrafluoroethylene reactor and place it in a vacuum drying oven. After hydrothermal reaction at 160 °C for 6 h, cool the solution and remove insoluble substances by filtration. Then place the filtrate in a dialysis bag and dialyze for 48 h. Freeze dry to obtain NP-CQDs solution. 2) Preparation of flame-retardant polyester fibers: After impregnating the polyester fiber with the NP-CQDs solution obtained in step 3), the polyester fiber is weighed. When its weight increases by 7%, flame-retardant polyester fiber is obtained. 3) Preparation of TPU film: 500g of pure TPU masterbatch was weighed and dried in a forced-air drying oven at 120℃ for 8 hours. Then, it was placed in a casting machine to cast a flame-retardant TPU film with a thickness of 0.8mm. The temperature of the feeding section of the twin-screw granulator was 110℃, the temperature of the mixing section was 130℃, the temperature of the extrusion section was 155℃, and the temperature of the die head was 135℃. The diameter of the roller used for casting was 500mm, the roller temperature was 45℃, and the film was wound on a 58A liquid silicone roller with a pressure of 6 kgf. 4) Preparation of the internal flame-retardant polyester fiber membrane: A 0.8mm thick layer of flame-retardant polyester fiber is laid between two pure TPU film layers. Then, it is placed in a molding machine and hot-pressed at 150℃ for 150 minutes, followed by cold pressing at room temperature for 10 minutes to form a composite film with multiple flame-retardant spaces.

[0046] Comparative Example 4 (Flame-retardant TPU film layer and flame-retardant polyester fiber with only BG added) A composite membrane with multiple flame-retardant spaces is prepared by the following steps: 1) Preparation of intumescent flame retardants: 50 mL of n-butanol was placed in a 250 mL three-necked flask, and 1.25 g of potassium hydroxide was added. The mixture was sonicated for 0.5 h to fully dissolve the potassium hydroxide. Then, 12.6 g of benzonitrile and 12.5 g of dicyandiamide were added, and the mixture was transferred to an oil bath. The mixture was reacted at 110 °C for 2 h under reflux cooling. During the reaction, a fine white solid gradually precipitated out. Heating was then stopped, and the mixture was cooled to room temperature. The product was washed several times with deionized water to remove unreacted dicyandiamide and dried at 60 °C for 24 h to obtain BG. 2) Preparation of flame-retardant TPU film: 35g of BG obtained in step 1) (accounting for 7% of the total) and 470g of pure TPU masterbatch were mixed in a small high-speed mixer at 600r / min for 0.5h. Then, the dried material was fed into a twin-screw granulator through the side feed port for extrusion granulation to produce flame-retardant TPU masterbatch. After drying at 120℃ for 8h, it was placed in a casting machine to cast a flame-retardant TPU film layer containing BG with a thickness of 0.8mm. The temperature of the feeding section of the twin-screw granulator was 110℃, the temperature of the mixing section was 130℃, the temperature of the extrusion section was 155℃, and the die head temperature was 135℃. The roller diameter used for casting was 500mm, the roller temperature was 45℃, and the roller was wound on a 58A liquid silicone roller with a pressure of 6Kgf. 3) Preparation of phosphorus-nitrogen doped quantum dot (NP-CQDs) solution: Weigh 1 g of glucose and place it in a 250 mL beaker. Add 25 mL of deionized water and sonicate for 0.5 h to dissolve it completely. Then add 0.8 mL of phytic acid and 0.5 mL of triethylamine and sonicate for another 0.5 h. Transfer the solution to a polytetrafluoroethylene reactor and place it in a vacuum drying oven. After hydrothermal reaction at 160 °C for 6 h, cool the solution and remove insoluble substances by filtration. Then place the filtrate in a dialysis bag and dialyze for 48 h. Freeze dry to obtain NP-CQDs solution. 4) Preparation of flame-retardant polyester fibers: After impregnating the polyester fiber with the NP-CQDs solution obtained in step 3), the polyester fiber is weighed. When its weight increases by 7%, flame-retardant polyester fiber is obtained. 5) Preparation of composite membranes with multi-layered flame-retardant spaces: A 0.8mm thick layer of flame-retardant polyester fiber is laid between two layers of flame-retardant TPU film containing BG. The film is then placed in a molding machine and hot-pressed at 150℃ for 150 minutes, followed by cold pressing at room temperature for 10 minutes to form a composite film with multiple flame-retardant spaces.

[0047] Comparative Example 5 (only LF-BPOD flame-retardant TPU film layer and flame-retardant polyester fiber added) A halogen-free flame-retardant TPU composite material, the preparation steps of which are as follows: 1) Preparation of halogen-free flame retardants: 1 g of lignin was dissolved in 60 mL of DMF and placed in a 250 mL three-necked flask. The solution was sonicated until fully dissolved and then transferred to a water bath. Under rapid stirring at room temperature, 4 g of BPOD was dispersed in 20 mL of DMF and transferred to a separatory funnel. Then, under a nitrogen atmosphere, 4 g of triethylamine was added as an acid-binding agent, and the flow rate was controlled so that the BPOD DMF dispersion was slowly added dropwise to the three-necked flask over 0.5 h. The reaction was then carried out under condensation, a nitrogen atmosphere, and 80 °C for 5 h. After the reaction was completed, the mixture was cooled to room temperature and centrifuged. The product was washed with chloroform, anhydrous ethanol, and deionized water to remove excess unreacted BPOD. The purified product was dissolved in deionized water and freeze-dried to obtain LF-BPOD. 2) Preparation of flame-retardant TPU film: 35g of BG / LF-BOPD (7% of the total amount) obtained in step 1) was mixed with 465g of pure TPU masterbatch in a small high-speed mixer at 600r / min for 0.5h. The dried material was then fed into a twin-screw granulator through a side feed port for extrusion granulation to produce flame-retardant TPU masterbatch. After drying at 120℃ for 8h, it was placed in a casting machine to cast a flame-retardant TPU film layer containing LF-BOPD with a thickness of 0.8mm. The temperature of the feeding section of the twin-screw granulator was 110℃, the temperature of the mixing section was 130℃, the temperature of the extrusion section was 155℃, and the die head temperature was 135℃. The roller diameter used for casting was 500mm, the roller temperature was 45℃, and the roller was wound on a 58A liquid silicone roller with a pressure of 6Kgf. 3) Preparation of phosphorus-nitrogen doped quantum dot (NP-CQDs) solution: Weigh 1 g of glucose and place it in a 250 mL beaker. Add 25 mL of deionized water and sonicate for 0.5 h to dissolve it completely. Then add 0.8 mL of phytic acid and 0.5 mL of triethylamine and sonicate for another 0.5 h. Transfer the solution to a polytetrafluoroethylene reactor and place it in a vacuum drying oven. After hydrothermal reaction at 160 °C for 6 h, cool the solution and remove insoluble substances by filtration. Then place the filtrate in a dialysis bag and dialyze for 48 h. Freeze dry to obtain NP-CQDs solution. 4) Preparation of flame-retardant polyester fibers: After impregnating the polyester fiber with the NP-CQDs solution obtained in step 3), the polyester fiber is weighed. When its weight increases by 7%, flame-retardant polyester fiber is obtained. 5) Preparation of halogen-free flame-retardant TPU composite film: A layer of flame-retardant polyester fiber with a thickness of 0.8 mm is laid between two layers of flame-retardant TPU film containing LF-BPOD. Then, it is placed in a molding machine and hot-pressed at 150℃ for 150 min, followed by cold pressing at room temperature for 10 min to form a composite film with multiple flame-retardant spaces.

[0048] Comparative Example 6 (Single-layer flame-retardant TPU film and flame-retardant polyester fiber) A composite membrane with a double-layer flame-retardant space is prepared by the following steps: 1) Preparation of intumescent flame retardants: a) Place 50 mL of n-butanol in a 250 mL three-necked flask, add 1.25 g of potassium hydroxide, and sonicate for 0.5 h to fully dissolve the potassium hydroxide. Then add 12.6 g of benzonitrile and 12.5 g of dicyandiamide, and transfer to an oil bath. React at 110 °C for 2 h under reflux cooling. During this period, a white fine solid gradually precipitates out. Then stop heating, cool to room temperature, and wash the product with deionized water several times to remove unreacted dicyandiamide. Dry at 60 °C for 24 h to obtain BG. b) Dissolve 1 g of lignin in 60 mL of DMF and place it in a 250 mL three-necked flask. Sonicate the solution until fully dissolved, and then transfer it to a water bath. Under rapid stirring at room temperature, disperse 4 g of BPOD in 20 mL of DMF and transfer it to a separatory funnel. Then, under a nitrogen atmosphere, add 4 g of triethylamine as an acid-binding agent and control the flow rate so that the BPOD DMF dispersion is slowly added dropwise to the three-necked flask over 0.5 h. React under condensation, nitrogen atmosphere, and 80 °C for 5 h. After the reaction is complete, cool to room temperature and centrifuge. Wash the product with chloroform, anhydrous ethanol, and deionized water to remove excess unreacted BPOD. Dissolve the purified product in deionized water and freeze-dry to obtain LF-BPOD. c) Add the BG obtained in step a) and the LF-BPOD obtained in step b) to a high-speed mixer at a mass ratio of 5:5, and stir and mix for 0.5 h to obtain BG / LF-BOPD. 2) Preparation of flame-retardant TPU film: 35g of BG / LF-BOPD (7% of the total amount) obtained in step 1) was mixed with 465g of pure TPU masterbatch in a small high-speed mixer at 600r / min for 0.5h. The dried material was then fed into a twin-screw granulator through a side feed port for extrusion granulation to produce flame-retardant TPU masterbatch. After drying at 120℃ for 8h, it was placed in a casting machine to cast a flame-retardant TPU film with a thickness of 0.8mm. The temperature of the feeding section of the twin-screw granulator was 110℃, the temperature of the mixing section was 130℃, the temperature of the extrusion section was 155℃, and the die head temperature was 135℃. The roller diameter used for casting was 500mm, the roller temperature was 45℃, and the film was wound on a 58A liquid silicone roller with a pressure of 6Kgf. 3) Preparation of phosphorus-nitrogen doped quantum dot (NP-CQDs) solution: Weigh 1 g of glucose and place it in a 250 mL beaker. Add 25 mL of deionized water and sonicate for 0.5 h to dissolve it completely. Then add 0.8 mL of phytic acid and 0.5 mL of triethylamine and sonicate for another 0.5 h. Transfer the solution to a polytetrafluoroethylene reactor and place it in a vacuum drying oven. After hydrothermal reaction at 160 °C for 6 h, cool the solution and remove insoluble substances by filtration. Then place the filtrate in a dialysis bag and dialyze for 48 h. Freeze dry to obtain NP-CQDs solution. 4) Preparation of flame-retardant polyester fibers: After impregnating the polyester fiber with the NP-CQDs solution obtained in step 3), the polyester fiber is weighed. When its weight increases by 7%, flame-retardant polyester fiber is obtained. 5) Preparation of composite membranes with double-layer flame-retardant spaces: A layer of flame-retardant polyester fiber with a thickness of 0.8 mm is laid on a layer of flame-retardant TPU film, and then it is placed in a molding machine. After hot pressing at 150℃ for 150 min, it is cold pressed at room temperature for 10 min to form a composite film with a double flame-retardant space.

[0049] The TPU test strips obtained from the examples and comparative examples were subjected to performance tests, and the results are shown in Table 1.

[0050] Table 1 Performance Test Results

[0051] As shown in Table 1, in Examples 1-5, the tensile mechanical properties of the composite membrane with multi-layer flame-retardant spaces were significantly improved with increasing dosages of flame retardants BG / LF-BPOD and NP-CQDs. Data from Comparative Examples 1-6 indicate that increasing the number of different flame-retardant membrane layers all contribute to improving the mechanical properties of the composite membrane; therefore, the multi-layer composite membrane exhibits higher mechanical properties compared to the double-layer composite membrane. Furthermore, with increasing dosages of flame retardants BG / LF-BPOD and NP-CQDs, the flame-retardant properties, heat resistance, and limiting oxygen index continuously improve. Therefore, it can be concluded that flame retardants BG / LF-BPOD and NP-CQDs possess good biocompatibility and can enhance the flame-retardant performance of the membrane.

[0052] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made within the scope of the claims of the present invention should be included in the scope of the present invention.

Claims

1. A method for preparing a composite membrane for inflatable boats, characterized in that: Includes the following steps: 1) Preparation of intumescent flame retardants: a) Place 50 mL of n-butanol in a 250 mL three-necked flask, add 1.25 g of potassium hydroxide, and sonicate for 0.5 h to fully dissolve the potassium hydroxide. Then add 12.6 g of benzonitrile and 12.5 g of dicyandiamide, and transfer to an oil bath. React at 110 °C for 2 h under reflux cooling. During this period, a white fine solid gradually precipitates out. Then stop heating, cool to room temperature, and wash the product with deionized water several times to remove unreacted dicyandiamide. Dry at 60 °C for 24 h to obtain BG. b) Dissolve 1 g of lignin in 60 mL of DMF and place it in a 250 mL three-necked flask. Sonicate the solution until fully dissolved, and then transfer it to a water bath. Under rapid stirring at room temperature, disperse 4 g of BPOD in 20 mL of DMF and transfer it to a separatory funnel. Then, under a nitrogen atmosphere, add 4 g of triethylamine as an acid-binding agent and control the flow rate so that the BPOD DMF dispersion is slowly added dropwise to the three-necked flask over 0.5 h. React under condensation, nitrogen atmosphere, and 80 °C for 5 h. After the reaction is complete, cool to room temperature and centrifuge. Wash the product with chloroform, anhydrous ethanol, and deionized water to remove excess unreacted BPOD. Dissolve the purified product in deionized water and freeze-dry to obtain LF-BPOD. c) Add the BG obtained in step a) and the LF-BPOD obtained in step b) to a high-speed mixer at a mass ratio of 5:5, and stir and mix for 0.5 h to obtain BG / LF-BOPD. 2) Preparation of flame-retardant TPU film: 35g of BG / LF-BOPD obtained in step 1) and 465g of pure TPU masterbatch were mixed in a small high-speed mixer at 600r / min for 0.5h. The dried material was then fed into a twin-screw granulator through a side feed port for extrusion granulation to produce flame-retardant TPU masterbatch. After drying at 120℃ for 8h, the masterbatch was placed in a casting machine to cast a flame-retardant TPU film with a thickness of 0.8mm. The temperature of the feeding section of the twin-screw granulator was 110℃, the temperature of the mixing section was 130℃, the temperature of the extrusion section was 155℃, and the die head temperature was 135℃. The roller diameter used for casting was 500mm, the roller temperature was 45℃, and the film was wound on a 58A liquid silicone roller with a pressure of 6Kgf. 3) Preparation of phosphorus and nitrogen doped quantum dot (NP-CQD) solution: Weigh 1 g of glucose and place it in a 250 mL beaker. Add 25 mL of deionized water and sonicate for 0.5 h to dissolve it completely. Then add 0.8 mL of phytic acid and 0.5 mL of triethylamine and sonicate for another 0.5 h. Transfer the solution to a polytetrafluoroethylene reactor and place it in a vacuum drying oven. After hydrothermal reaction at 160 °C for 6 h, cool the solution and remove insoluble substances by filtration. Then place the filtrate in a dialysis bag and dialyze for 48 h. Freeze dry to obtain NP-CQDs solution. 4) Preparation of flame-retardant polyester fibers: After impregnating the polyester fiber with the NP-CQDs solution obtained in step 3), the polyester fiber is weighed. When its weight increases by 7%, flame-retardant polyester fiber is obtained. 5) Preparation of composite membranes with multi-layered flame-retardant spaces: A layer of flame-retardant polyester fiber with a thickness of 0.8 mm is laid between two layers of flame-retardant TPU film. Then, it is placed in a molding machine and hot-pressed at 150°C for 150 minutes, followed by cold pressing at room temperature for 10 minutes to form a composite film with multiple flame-retardant spaces.

Citation Information

Patent Citations

  • Lightweight fiber reinforced thermoplastic composite board and preparation method thereof

    CN109263181A

  • Flame-retardant polyester fiber fabric and preparation method thereof

    CN115679470A

  • Low-smoke flame-retardant base film for environment-friendly floor leather surface layer and preparation method of low-smoke flame-retardant base film

    CN116082825A